2019
DOI: 10.1016/j.ijfatigue.2019.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Thermomechanical fatigue behaviour of aged heat resistant austenitic alloys

Abstract: The increasing demands for efficiency and flexibility result in more severe operating conditions for the materials used in critical components of biomass power plants. These operating conditions involve higher temperature ranges, more pronounced environmental effects and cyclic operations. Austenitic stainless steels have shown to possess promising high temperature properties which makes them suitable as candidates for critical components in biomass power plant. However, their behaviour under such conditions i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…The initial microstructure of this Sanicro 25 alloy (i.e. after annealing at 1200°C for 1 h) has been studied earlier by Heczko et al 10,11,26 and Warner et al 27 . The average grain size of 60 μm was determined by the intercept method; however, large grains of the size up to 200 μm were present as well.…”
Section: Microstructurementioning
confidence: 91%
See 1 more Smart Citation
“…The initial microstructure of this Sanicro 25 alloy (i.e. after annealing at 1200°C for 1 h) has been studied earlier by Heczko et al 10,11,26 and Warner et al 27 . The average grain size of 60 μm was determined by the intercept method; however, large grains of the size up to 200 μm were present as well.…”
Section: Microstructurementioning
confidence: 91%
“…Laves phases were also found in the microstructural study of the specimens Sanicro 25 exposed to 700°C for 3000 hours reported by Chai et al 2 . Warner et al 27 investigated thermomechanical behaviour of virgin and pre-aged specimens subjected to IP-TMF loading in the temperature range from 100°C to 800°C. Microstructural investigation revealed the formation of Nb(C,N), Z-phase, Cr 2 N, M 23 C 6 and μ-phase in virgin specimens while strained pre-aged specimens resulted in the extra formation of Laves phase (Fe,Cr) 2 W. Precipitates having larger dimensions and lower density like tungsten carbides or Z-phase do not affect substantially the material strength.…”
Section: Internal Structurementioning
confidence: 99%
“…The initial microstructure of Sanicro 25 alloy (i.e., after annealing at 1200 C for 1 h) has been studied earlier by Heczko et al 35,36,46 and Warner et al 25 The average grain size of 60 μm was determined by the intercept method; however, large grains of the size up to 200 μm were present as well. The characteristic attribute of the dislocation structure before applying cyclic loading is planar dislocation arrangement consisting of individual dislocations, stacking faults, pile-ups, and so forth.…”
Section: Microstructurementioning
confidence: 99%
“…The most severe loading conditions are those where stress or strain and temperature vary simultaneously, that is, in the case of thermomechanical fatigue. Numbers of thermomechanical studies were devoted to superalloy single and polycrystals 5–13 and to austenitic, low alloyed ferritic and dual hardening steels 14–28 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation